Intragenerational inequality aversion and intergenerational equity - Vincent Martinet; Stellio Del Campo; Robert D. Cairns (European Economic Review, 2022)
We study the interplay between intragenerational and intergenerational equity in an economy with two countries producing and consuming from national capital stocks. We characterize the sustainable development path that a social planner would implement to achieve intertemporal egalitarianism. If intergenerational equity is defined with respect to the global consumption of each generation regardless of its distribution between countries, consumption in the poor country should be set as low as possible to maximize investment and hasten convergence, resulting in important intragenerational inequality. When social welfare accounts for intragenerational equity, the larger the intragenerational inequality aversion (IIA), the smaller the sacrifice asked of the poor country, but the lower the sustained level of generational welfare. Along the intertemporal welfare-egalitarian path with IIA, consumption in the poor country increases, while it decreases in the rich country, resulting in a global degrowth.
Keywords: O44; Q56; 330; Sustainable development; Intergenerational egalitarianism; Maximin; Intragenerational inequality; Differentiated degrowth